PENGARUH MOTIVASI DAN PENGETAHUAN UNDANG-UNDANG NO.5 TAHUN 2011 TENTANG AKUNTAN PUBLIK TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI (Studi Kasus Pada Mahasiswa Akuntansi Universitas Riau, Universitas Islam Negeri Sultan Syarif Kasim Riau, Universitas Islam Riau dan Universitas Lancang Kuning) - Septi Indriyani; Nur Azlina; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to find and obtain empirical evidence about the factors that affect the interests of accounting students to follow PPAk. Respondents in this study are students majoring in accounting who are studying strata 1 at the University of Riau, UIN Sultan Syarif Kasim, Islamic University of Riau, and the University of Lancang Kuning. The method of determining the samples used in this study is purposive sampling, while the method of data collection using questionnaire method with the number of students who become the sample of this study is 93 students from four universities. This research is a quantitative model with data analysis method including validity test, reliability test, normality test, classical assumption test: heteroscedasticity and multicolinearity, determinant coefficient test and hypothesis test: t test using SPSS 21.00 for data processing. The results of this study indicate that career motivation, quality motivation, and knowledge of Law number 5 of 2011 on public accountants affect the interest of accounting students to follow PPAk. Meanwhile, economic motivation does not affect the interest of accounting students to follow the education of accounting professions.Keywords: interest, motivation, career motivation, quality motivation, economic motivation, knowledge of Law number 5 of 2011 on public accountant, interest to follow the education of accounting professions